Demystifying work-related outcomes and life satisfaction of Bangladeshi working women during the COVID-19 pandemic - Shajjad Mahmod (Annals of Management and Organization Research, 2022)
Purpose: The impact of the COVID-19 outbreak on working women’s personal and professional lives is overwhelming. This paper aims to demystify the intervening role of work-life balance in the association of life satisfaction with work-from-home and workplace flexibility during a covid emergency. Research methodology: To follow this aim, 196 working women coming from different occupations enjoying work-from-home arrangements during COVID-19 have been selected based on convenience as respondents. After confirming the reliability-validity and fitness of the proposed model, the responses have been further examined for testing the hypotheses. Results: The findings demystify strong associations of independent variables (work from home and workplace flexibility) with the dependent variable (life satisfaction) as well as with the mediator (work-life balance). The mediating role of work-life balance between the independent and dependent variables has also proved significant. Limitations: This study has limitations, such as mainly focusing on Chattagram, Bangladesh, selecting respondents based on convenience, and needing more research to analyse the effects of variables on male workers. Contribution: Regulatory authorities, corporate bodies and HR practitioners will get strong insights while formulating strategic HR guidelines in regular situations as well as in emergencies in this study. Novelty: In a patriarchal country like Bangladesh, where women's contributions to the economy are increasing day by day, the government and other regulatory authorities should consider working women's work-life equilibrium and well-being when drafting legislation regarding HR practices.